2018
DOI: 10.1136/jech-2018-210672
|View full text |Cite
|
Sign up to set email alerts
|

Avoidable mortality among parents whose children were placed in care in Sweden: a population-based study

Abstract: Parents who had a child placed in out-of-home care are at higher risk of avoidable mortality. Interventions targeting mothers who had a child aged less than 13 placed in care, and parents whose children were all placed in care could have the greatest impact in reducing avoidable mortality in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
1
8
0
1
Order By: Relevance
“…In this study, we did not attempt adjustment for other risk factors for premature death as we were limited to answering how mortality rates differed between our study cohort and matched controls rather than why they differed. Previous research into deaths among women whose children entered care in Manitoba, Canada and Sweden found that the association between entry into care and death remains after adjusting for other mortality risk factors [17,42,43]. These studies also used several control group methods including biological sisters and women whose children died.…”
Section: Findings In Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we did not attempt adjustment for other risk factors for premature death as we were limited to answering how mortality rates differed between our study cohort and matched controls rather than why they differed. Previous research into deaths among women whose children entered care in Manitoba, Canada and Sweden found that the association between entry into care and death remains after adjusting for other mortality risk factors [17,42,43]. These studies also used several control group methods including biological sisters and women whose children died.…”
Section: Findings In Contextmentioning
confidence: 99%
“…Population-based characterisation of maternal mental health need and service use among birth mothers is needed, yet suitable data are lacking [16]. In several settings, researchers have overcome this barrier by linking administrative child protection and health datasets [17][18][19][20][21]. Within the SAIL Databank, Griffiths et al used new linkages between Welsh family court data and health data on antenatal care, hospitalisations and general practitioner (GP) contacts, and found high prevalence of maternal mental health difficulties in the 2 years prior to childbirth [22].…”
Section: Introductionmentioning
confidence: 99%
“…we matched on few variables and adjusted only for age), previous research into deaths among women whose children entered care in Manitoba, Canada and Sweden has shown that higher rates of death remain after adjusting for other mortality risk-factor and different control groups such as biological sisters or women whose children died. [14,47,48] Strengths and limitations This is one of the first UK studies to describe maternal mental health service use among women involved in care proceedings, focused on England. Though the SLaM population may vary in terms of population demographics and service availability from other parts of the UK -potentially affecting the generalisability of these findings -we found similarly high rates of mental health need among women in proceedings as were found in Wales.…”
Section: Findings In Contextmentioning
confidence: 99%
“…To provide evidence on parental health in the context of child protection, many high-income countries and regions have successfully established linkages between data collected by child protection systems and administrative health data sets. [14][15][16][17][18] In South Australia, for example, the state government has worked together with researchers and local Aboriginal and Torres Strait Islander communities to establish a state-wide linkage project -the South Australia Early Childhood Data Project. [19] As well as being used for research, this linkage has directly informed redesign of the South Australian Child and Family Health Service in response to calls to improve and widen its support for families to reduce the need for child protection intervention.…”
Section: Introductionmentioning
confidence: 99%
“…6 In Canada and Sweden, national mortality data report that birth parents who have children removed are over three times more likely to die of a preventable cause compared to their biological siblings 16 or to other parents. 17 …”
Section: Introductionmentioning
confidence: 99%